Expanded syringe exchange programs and reduced HIV infection among new injection drug users in Tallinn, Estonia - Abel-Ollo Katri; Rüütel Kristi; Kals Mart; Des Jarlais Don C; Uusküla Anneli; Talu Ave; Sobolev Igor (BMC, 2011)
Abstract Background Estonia has experienced an HIV epidemic among intravenous drug users (IDUs) with the highest per capita HIV prevalence in Eastern Europe. We assessed the effects of expanded syringe exchange programs (SEP) in the capital city, Tallinn, which has an estimated 10,000 IDUs. Methods SEP implementation was monitored with data from the Estonian National Institute for Health Development. Respondent driven sampling (RDS) interview surveys with HIV testing were conducted in Tallinn in 2005, 2007 and 2009 (involving 350, 350 and 327 IDUs respectively). HIV incidence among new injectors (those injecting for < = 3 years) was estimated by assuming (1) new injectors were HIV seronegative when they began injecting, and (2) HIV infection occurred at the midpoint between first injection and time of interview. Results SEP increased from 230,000 syringes exchanged in 2005 to 440,000 in 2007 and 770,000 in 2009. In all three surveys, IDUs were predominantly male (80%), ethnic Russians (>80%), and young adults (mean ages 24 to 27 years). The proportion of new injectors decreased significantly over the years (from 21% in 2005 to 12% in 2009, p = 0.005). HIV prevalence among all respondents stabilized at slightly over 50% (54% in 2005, 55% in 2007, 51% in 2009), and decreased among new injectors (34% in 2005, 16% in 2009, p = 0.046). Estimated HIV incidence among new injectors decreased significantly from 18/100 person-years in 2005 and 21/100 person-years in 2007 to 9/100 person-years in 2009 (p = 0.026). Conclusions In Estonia, a transitional country, a decrease in the HIV prevalence among new injectors and in the numbers of people initiating injection drug use coincided with implementation of large-scale SEPs. Further reductions in HIV transmission among IDUs are still required. Provision of 70 or more syringes per IDU per year may be needed before significant reductions in HIV incidence occur.